A Milestone in Environmental and Future Generations' Rights Protection: Recent Legal Developments before the Colombian Supreme Court. (16th October 2018) - Acosta Alvarado, Paola Andrea; Rivas-Ramírez, Daniel
ABSTRACT: In April 2018, the Colombian Supreme Court reached an historic decision concerning the deforestation problem in the Colombian Amazon Rainforest. The case STC 4360-2018 raises many legal dilemmas concerning the relationship between deforestation and constitutional rights recognised by the Colombian constitution, including the right to life, the right to human health, and the right to a healthy environment. In this analysis, we discuss how the Supreme Court's ruling represents heterodox legal reasoning grounded in 'de-colonial' thinking; the impact of international environmental law on the Court's findings; and the implications that the judgment may have on the Colombian legal order, focusing in particular on the way that the Court seems to promote the protection of collective rights over private rights.